Competition and Commercial Banks Risk-Taking: Evidence from Sub-Saharan Africa Region - Akande JO; Kwenda F; Ehalaiye D (Taylor and Francis Group)
This study investigates the relationship between competition and the risk-taking attitude of banks. We test how this relationship manifests in the Sub-Saharan African(SSA) region’s commercial banks in light of the competition-fragility view, using the generalized methods of moments. We studied 440 commercial banks in 37 SSA countries over the period 2006–2015. The results provide evidence that supports a positive relationship between competition and banks’ overall risk as well as their credit risk but suggests that off-balance sheet risk reduces with competition. We, therefore, conclude that the propensity to undertake higher risk in a competitive banking environment largely accounts for fragility as argued in the competition-fragility view.
Keywords: Competition; risk-taking behaviour; Lerner index; generalized method of moments; commercial banks; G21; G29; L10; 1402 Applied Economics; 1403 Econometrics; 1502 Banking, Finance and Investment